Perdagangan Bilateral Filipina-Amerika: Dinamika, Hambatan dan Prospek Masa Depan Periode 2022-2024 - Rizky, Ramadhan Bagas; Alya, Haura Inas; Rahmatulummah, Alia (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
This study examines the dynamics of trade relations between the Philippines and the United States during the leadership of President Bongbong Marcos, the 17th President of the Philippines. The primary objective of this research is to identify obstacles, challenges, and opportunities in the bilateral relations of the two nations, with a particular focus on political, economic, and security aspects. Employing the theories of liberalism and complex interdependence, the study explores how economic cooperation and mutual dependence influence trade policy relations between the Philippines and the United States. The research uses a qualitative descriptive method, involving an in-depth analysis of data and information related to trade policies, bilateral agreements, and external factors that may affect relations during President Bongbong Marcos's administration. The findings reveal that, despite progress in trade cooperation, obstacles such as protectionist policies and global economic instability remain significant challenges. Future prospects indicate substantial growth potential if both nations can overcome these barriers through constructive dialogue and mutually beneficial policy reforms. A limitation of this study lies in the uncertainty of Philippine-U.S. relations due to frequent political dynamics. However, the impact of this research lies in its ability to anticipate the continuation of Philippine-U.S. relations through insights derived from field data.